Validation of reliability and validity of the Chinese version of the active-empathic listening scale - Guo, Hang; Lin, Lemin; Jia, Ziming; Sun, Jiaying; Zhuang, Zisen; Duan, Lisa; Sun, Jiangnan (Frontiers in Psychiatry, 2022)
Abstract Background: Active-empathic listening (AEL) is the active and emotional involvement of a listener that can take place in at least three key stages of the listening process. Bodie has developed and validated a self-reported, 11-item, three-factor Active-Empathic Listening Scale (AELS) in English with good reliability (Cronbach’s alpha = 0.86) to assess active-empathic listening abilities. Nevertheless, a Chinese version of the AELS had not been established and validated yet. Objective: The objective of the present study was to examine the reliability and validity of the Chinese version of the Active-empathic listening scale (AELS). Methods: After translating the scale into Chinese version, 834 college students completed the Chinese AELS and the Interpersonal Reactivity Index (IRI). After 4 weeks, 206 participants were tested again on the Chinese AELS to examine retest reliability. The critical ratio method and the item-total correlations were used for the item analysis. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed to examine the construct validity. The internal consistency of the scale was analyzed with Cronbach’s alpha and McDonald's Omega. Interclass correlation coefficient (ICC) was used to examine the scale's retest reliability. To examine convergent validity, Pearson correlation analysis was conducted. Results: Each item of the Chinese AELS had a good discrimination, and the item-total correlation of each item ranged from 0.51 to 0.73. EFA extracted 3 factors with characteristic root value greater than 1, which could explain 70.72% of the total variance. CFA indicated an adequate fit of the three-factor model (χ2/df=2.250, RMSEA=0.055, CFI=0.971, TLI=0.959, GFI=0.959). The internal consistency reliability was acceptable (Sensing: α =0.79/ =0.78, Processing: α =0.83/ =0.83, Responding: α =0.79/ =0.79, AELS: α = 0.87/ =0.87). Retest reliability of the scale at 4-week intervals by an ICC was 0.563. The Chinese AELS was significantly correlated with each dimension of IRI. Conclusion: The reliability and validity of the Chinese AELS met the basic psychometrics requirements. Therefore, the scale can be potentially used to assess active empathic listening abilities of people in China.